2013
DOI: 10.1174/021093913806751438
|View full text |Cite
|
Sign up to set email alerts
|

Strategy instruction for writing composition at school and at home

Abstract: The objectives of this study are 1) to analyze the effectiveness of a writing composition intervention program aimed to increase children's writing performance and other personal variables; 2) to analyze whether implementation in the environment (school and home) or responsible figures (parents and teachers) produced different effects in program effectiveness; and 3) to check whether increasing parental involvement in doing homework was sufficient to improve children's outcomes or whether prior family training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
5
0
7
Order By: Relevance
“…A sizeable number of studies examined the effects of coproduction on knowledge acquisition. A wide variety of effects have been measured: maths scores and the extent to which parents show that they are interested in maths education (Martin et al, 2015;Sheldon et al, 2010); the effects of involving parents in literacy programmes (Altschul, 2011;Robledo-Ramon and Garc ıa Sanchez, 2013;Sylva et al, 2008) and the effects of home visits (Stetson et al, 2012).…”
Section: Empirical Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizeable number of studies examined the effects of coproduction on knowledge acquisition. A wide variety of effects have been measured: maths scores and the extent to which parents show that they are interested in maths education (Martin et al, 2015;Sheldon et al, 2010); the effects of involving parents in literacy programmes (Altschul, 2011;Robledo-Ramon and Garc ıa Sanchez, 2013;Sylva et al, 2008) and the effects of home visits (Stetson et al, 2012).…”
Section: Empirical Papersmentioning
confidence: 99%
“…Some programmes were developed to raise the language, maths or writing skills of pupils, others to train and empower parents, yet others to help parents and teachers develop joint strategies, rules and guidelines necessary to help children realize their full potential (see also Feiler et al, 2008). Programmes for parents to assist them in helping children with maths (Sheldon et al, 2010) and literacy (Bierman et al, 2008;Robledo-Ramon and Garc ıa Sanchez, 2013) were found to contribute to a significantly higher level of academic success (Robledo-Ramon and Garc ıa Sanchez, 2013).…”
Section: Empirical Papersmentioning
confidence: 99%
“…Diversas instrucciones e intervenciones en composición escrita se han realizado con énfasis en el producto (Frydrychova, 2014;Hasan y Akhand, 2010;Hashemnezhad y Hashemnezhad, 2012;Iandolo, Esposito, y Venuti, 2013;Koster et al, 2015;Nguyen y Abbott, 2016;Nordin y Mohammad, 2006;Shahrokhi, 2017). Estas se materializan en el análisis del desempeño, la ejecución, el éxito o el resultado final de la escritura atendiendo a diferentes indicadores, tales como la productividad o la cantidad de ideas del producto textual (García, Fidalgo, et al, 2014;Iandolo et al, 2013;Robledo y García, 2013); la estructura u organización de ideas que es inherente a la tipología textual (García, Fidalgo, et al, 2014;Graham y Sandmel, 2011;Iandolo et al, 2013;Thulasi, Bin, y Bte, 2014;Robledo y García, 2013); la coherencia definida como un representación mental del texto (García, Robledo, et al, 2014;Iandolo et al, 2013;Robledo y García, 2013), y sobre todo la calidad (Beauvais, Olive, y Passerault, 2011;García, Fidalgo, et al, 2014;Graham y Sandmel, 2011;Thulasi et al, 2014).…”
Section: Enfoques Instruccionales Virtuales: Proceso Y Productounclassified
“…Por otro lado, con los avances de la psicología de la escritura y el cambio de paradigma en la educación se produce una mayor preocupación no solo en los resultados, sino también en los procesos desplegados por el aprendiz. Las diferentes competencias básicas, ilustradas en la composición escrita, han sido definidas como una actividad compleja que implica la ejecución de tres grandes procesos (planificar, traducir o editar o ejecutar y revisar), convirtiéndose en el objeto de interés de numerosas investigaciones psicológicas instruccionales y concibiéndose como el eje angular para estudiar la cognición humana pero sobre todo los procesos y subprocesos que permiten ejecutarla, así como su dinámica, orquestación y recursividad requeridas (Graham y Sandmel, 2011;Hayes, 1996;Olive, Kellogg, y Piolat, 2001;Thulasi et al, 2014), dando lugar a intervenciones e instrucciones con énfasis en los procesos y variables psicológicas (Beauvais et al, 2011;Frydrychova, 2014;Hasan y Akhand, 2010;Hashemnezhad y Hashemnezhad, 2012;Koster et al, 2015;Nguyen y Abbott, 2016;Nordin y Mohammad, 2006;Robledo y García, 2013).…”
Section: Enfoques Instruccionales Virtuales: Proceso Y Productounclassified
See 1 more Smart Citation